Mrs Killer and Dr Crook: Birth Attendants and Birth Outcomes in Early Twentieth-century Derbyshire - Reid, Alice (Cambridge University Press, 2012)
After the passing of the 1902 Midwives Act, a growing proportion of women were delivered by trained and supervised midwives. Standards of midwifery should therefore have improved over the first three decades of the twentieth century, yet nationally this was not reflected in the main outcome measures (stillbirths, early neonatal mortality and maternal death). This paper shows that there was a difference in the risks associated with delivery by the different attendants, with qualified midwives having the best outcome, then bona-fide (untrained) midwives and lastly doctors, even when account is taken of the fact that doctors were called in cases of medical need and may have been booked where a problematic delivery was expected. The paper argues that the lack of improvement in outcome measures could be consistent with improving standards of care among both trained and bona-fide midwives, because increased attention to the rules stipulating when midwives called for medical help meant that a doctor was called into an increasing number of deliveries (including less complicated ones), raising the chance of unnecessary and dangerous interventions.